Therapeutic Potential of Polyscias fruticosa (L.) Harms Leaf Extract for Parkinson's Disease Treatment by Drosophila melanogaster Model. (19th May 2022) - Ly, Hai Trieu; Nguyen, Thi Thu Huong; Le, Van Minh; Lam, Bich Thao; Mai, Thi Thu Trinh; Dang, Thi Phuong Thao
Abstract : Parkinson's disease (PD) is characterized by progressive locomotive defects and loss of dopaminergic neurons. Polyscias fruticosa leaves are used by Vietnamese as herbal medicines to support the treatment of some diseases related to neurodegeneration such as Parkinson's and Alzheimer's diseases. However, recent scientific data have not provided sufficient evidence for the use of P. fruticosa leaves to treat PD or decelerate PD progression. In the present study, the capacity of P. fruticosa leaf extract for PD treatment on the dietary supplementation was investigated using dUCH-knockdown Drosophila model. The results indicated that P. fruticosa leaf extract decelerated dopaminergic neuron degeneration induced by dUCH knockdown in not only the larval stage but also the adult stage, which might result in the amelioration in locomotor ability of dUCH-knockdown larvae and flies. Furthermore, antioxidant activities and some key phytochemicals such as saponins, polyphenols, and flavonoids that might contribute to the effects of the P. fruticosa leaf extract were identified.